Perbedaan Intensitas Menonton Drama Korea antara Peserta Didik Laki-Laki dan Perempuan Kelas VIII di SMPN 11 Jakarta - Fajrin, Hardiani; Asni, Asni (Universitas Borneo Tarakan, 2024)
This research aims to identify and describe the differences in the intensity of watching Korean dramas between male and female students in class VIII at SMPN 11 Jakarta. The research method used is a qualitative research method with class VIII students as a sample which of the samples have specific criteria that have been determined by the researcher, namely class VIII students who often watch Korean dramas. Validity testing in this research uses the Pearson Product Moment Correlation formula with a total of 40 items. The results of the analysis state that there are 15 items that are invalid and the remaining 25 are valid. To test the reliability itself, the formula used is Alfa Cronbach with the acquisition value of 0.978 0.195, from which it can be concluded that it is reliable. After that, the data were analyzed with the prerequisite test in the form of the Normalistas test with the Klomogrov Smirnov formula. The significance value of the test results for the intensity variable using Instagram social media is 0.978 0.05, so it can be concluded that the data is normally distributed. The results of this research stated that the intensity of watching for male students was 99.96 while for female students it was 106.35. It can be concluded that there is a difference in the intensity of watching Korean dramas between male and female students in Class VIII at SMPN 11 Jakarta of 6.39.